2014
DOI: 10.1155/2014/612972
|View full text |Cite
|
Sign up to set email alerts
|

Association betweenNFKB1−94ins/del ATTG Promoter Polymorphism and Cancer Susceptibility: An Updated Meta-Analysis

Abstract: Nuclear factor-κB is associated with the pathogenesis of numerous malignancies, and the functional polymorphism −94ins/del ATTG (rs28362491) in the human NFKB1 gene is associated with cancer risk. Previous studies on the association between the −94ins/del ATTG polymorphism and cancer risk reported conflicting results. To clarify this relationship, we performed a meta-analysis of 21 case-control studies involving 6127 cases and 9238 controls. We used pooled odds ratios (ORs) with their 95% confidence intervals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 40 publications
2
27
4
Order By: Relevance
“… 14 A common deletion-allele in the promoter region of NF- κ B 1 results in lower protein levels of the NF-κB p50 subunit. NF- κ B1 94ATTG ins/del polymorphism was associated with risk of cancer 32 , 33 and CHD. 37 However, the present study did not find an interaction between NF- κ B1 94ATTG ins/del polymorphism and HTLV-I for the risk of total death or incidence of cancer and atherosclerosis-related diseases.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“… 14 A common deletion-allele in the promoter region of NF- κ B 1 results in lower protein levels of the NF-κB p50 subunit. NF- κ B1 94ATTG ins/del polymorphism was associated with risk of cancer 32 , 33 and CHD. 37 However, the present study did not find an interaction between NF- κ B1 94ATTG ins/del polymorphism and HTLV-I for the risk of total death or incidence of cancer and atherosclerosis-related diseases.…”
Section: Discussionmentioning
confidence: 96%
“…The associations between inflammatory gene polymorphisms and the development of ATLL 23 and HAM/TSP has been reported. 24 , 25 , 26 , 27 Interestingly, these polymorphisms were also associated with the development of not only several sites of cancer, 28 , 29 , 30 , 31 , 32 , 33 but also atherosclerosis-related diseases. 34 , 35 , 36 , 37 TNF- α , encoded by the TNF -α gene, is a cytokine responsible for resistance to infection and cancers and exerts major proinflammatory action by stimulating adhesion molecules and chemokine expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5), on the other hand, were connected with cancer, specifically prostate cancer signaling, and leptin signaling in obesity. Polymorphisms in nuclear factor of kappa light polypeptide gene enhancer in B-cells 1 (NFKB1) have been associated with development of prostate cancer [44,45].…”
Section: Transcriptome Profile Of Testes Affected By Testis Sizementioning
confidence: 99%
“…As a polygenic disease, the pathogen esis of ovarian cancer is multifactorial, which means that multiple genetic factors may be associated with its development and progression (Gulden and Olopade, 2010). Previous studies have suggested that polymorphisms in nuclear factor-kB (NF-kB), a transcription factor that is activated by various stimuli, may be associated with ovarian cancer (Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%